25-Hydroxycholesterol Inhibition of Lassa Virus Infection through Aberrant GP1 Glycosylation - Punya Shrivastava-Ranjan; Éric Bergeron; Ayan K. Chakrabarti; César G. Albariño; Mike Flint; Stuart T. Nichol; Christina F. Spiropoulou (mBio, 2016)
ABSTRACT Lassa virus (LASV) infection is a major public health concern due to high fatality rates and limited effective treatment. The interferon-stimulated gene cholesterol 25-hydroxylase (CH25H) encodes an enzyme that catalyzes the production of 25-hydroxycholesterol (25HC). 25HC is involved in regulating cholesterol biosynthesis and has recently been identified as a potent antiviral targeting enveloped virus entry. Here, we show a previously unrecognized role of CH25H in inhibiting LASV glycoprotein glycosylation and the production of infectious virus. Overexpression of CH25H or treatment with 25HC decreased LASV G1 glycoprotein N-glycan maturation and reduced the production of infectious LASV. Depletion of endogenous CH25H using small interfering RNA (siRNA) enhanced the levels of fully glycosylated G1 and increased infectious LASV production. Finally, LASV particles produced from 25HC-treated cells were found to be less infectious, to incorporate aberrantly glycosylated GP1 species, and to be defective in binding alpha-dystroglycan, an attachment and entry receptor. Our findings identify a novel role for CH25H in controlling LASV propagation and indicate that manipulation of the expression of CH25H or the administration of 25HC may be a useful anti-LASV therapy. IMPORTANCE Lassa fever is an acute viral hemorrhagic fever in humans caused by Lassa virus (LASV). No vaccine for LASV is currently available. Treatment is limited to the administration of ribavirin, which is only effective when given early in the course of illness. Cholesterol 25-hydroxylase (CH25H) is a recently identified interferon-stimulated gene (ISG); it encodes an enzyme that catalyzes the production of 25-hydroxycholesterol (25HC), which inhibits several viruses. Here, we identify a novel antiviral mechanism of 25HC that is dependent on inhibiting the glycosylation of Lassa virus (LASV) glycoprotein and reducing the infectivity of LASV as a means of suppressing viral replication. Since N-linked glycosylation is a critical feature of other enveloped-virus glycoproteins, 25HC may be a broad inhibitor of virus infectivity.